Tolerance factor and phase stability of the garnet structure. Corrigendum. Issue 3 (27th February 2020) - Song, Zhen; Zhou, Dandan; Liu, Quanlin
Abstract : Corrigendum to Acta Cryst. (2019), C75, 1353–1358 . Abstract : An error in an equation in the paper by Song et al. [ Acta Cryst. (2019), C75, 1353–1358 ] is corrected.